Pendidikan Berbasis Budaya : Sebuah Studi Literatur dalam Masyarakat Multikultural (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This research discusses the role of culture-based education in a multicultural society as well as the challenges and implementation strategies. Multicultural education aims to create an inclusive learning environment and integrate local cultural values in the curriculum. Using the literature study method, this research examines how a culture-based education approach can improve students' understanding of social diversity and build tolerant characters. The results show that despite challenges such as lack of cultural representation in teaching materials and unequal access to education, multicultural education has great benefits in building social awareness and nationalism. Strategies such as the use of simulation-based learning, adaptive teaching methods and culture-based curriculum development are solutions to these challenges. The implications of this research emphasize the importance of education that is responsive to cultural diversity in order to create a more harmonious and inclusive society.